Making sense of blood glucose data and self‐management in individuals with type 2 diabetes mellitus: A qualitative study. Issue 13 (27th April 2020) - Despins, Laurel A.; Wakefield, Bonnie J.
Abstract: Aims and objectives: To describe individuals' with type 2 diabetes mellitus sense‐making of blood glucose data and other influences impacting self‐management behaviour. Background: Type 2 diabetes mellitus prevalence is increasing globally. Adherence to effective diabetes self‐management regimens is an ongoing healthcare challenge. Examining individuals' sense‐making processes can advance staff knowledge of and improve diabetes self‐management behaviour. Design: A qualitative exploratory design examining how individuals make sense of blood glucose data and symptoms, and the influence on self‐management decisions. Methods: Sixteen one‐on‐one interviews with adults diagnosed with type 2 diabetes mellitus using a semi‐structured interview guide were conducted from March–May 2018. An inductive–deductive thematic analysis of data using the Sensemaking Framework for Chronic Disease Self‐Management was used. The consolidated criteria for reporting qualitative research (COREQ) checklist were used in completing this paper. Results: Three main themes described participants' type 2 diabetes mellitus sense‐making and influences on self‐management decisions: classifying blood glucose data, building mental models and making self‐management decisions. Participants classified glucose levels based on prior personal experiences. Participants learned about diabetes from classes, personal experience, health information technology and their social network. Seven participants expressed a need for periodic refreshing of diabetes knowledge. Conclusion: Individuals use self‐monitored glucose values and/or HbA1C values to evaluate glucose control. When using glucose values, they analyse the context in which the value was obtained through the lens of personal parameters and expectations. Understanding how individuals make sense of glycaemic data and influences on diabetes self‐management behaviour with periodic reassessment of this understanding can guide the healthcare team in optimising collaborative individualised care plans. Relevance to clinical practice: Nurses must assess sense‐making processes in self‐management decisions. Periodic "refresher" diabetes education may be needed for individuals with type 2 diabetes mellitus.